PENGARUH DIGITAL TRUST, ISLAMIC FINANCIAL LITERACY, DAN SERVICE EXPERIENCE TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK CICIL EMAS DAN GADAI EMAS DI BANK SYARIAH INDONESIA KANTOR CABANG MANADO MANTOS - Wanda Fauziyyah; Willem J. F. A. Tumbuan; Christoffel M. O. Mintardjo (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
The increase in gold prices over the past year has contributed to a growing public interest in investment, in line with government policies through the establishment of a Gold Bank. As the first gold bank in Indonesia, Bank Syariah Indonesia provides comprehensive services, ranging from trading and sales to gold custody. In this context, this study aims to analyze the influence of Digital Trust, Islamic Financial Literacy, and Service Experience on purchase decisions for Gold Installment and Gold Pawn products at Bank Syariah Indonesia, Manado Mantos Branch Office. The sample was determined using a purposive sampling technique, with a population of 829 customers, and based on the Slovin formula, 89 respondents were selected as the research sample. This study employed a quantitative approach with analytical techniques including validity testing, reliability testing, classical assumption testing, hypothesis testing, and multiple linear regression analysis. The results indicate that simultaneously, Digital Trust, Islamic Financial Literacy, and Service Experience have a significant effect on purchase decisions. Partially, each of these variables also has a positive and significant influence on purchase decisions. This study contributes theoretically by enriching the literature on consumer behavior in Islamic banking and practically serves as a reference for Bank Syariah Indonesia in enhancing digital trust, Islamic financial literacy, and service experience quality to encourage customers’ purchase decisions for gold products.